Contextualization of Qiwamah Meaning: Reflection on Abdullah Saeed, Application and Consistency - Musfiroh, Mayadina Rohmi; Syamsuddin, Sahiron (UIN Sunan Kudus, 2020)
Textual interpretation potentially emerges conflict because it denies the social cultural context in which Al-Qur’an is used a way of life in the present context. Especially if the verse interpreted textually is related to the division of roles and rights that must be fulfilled in a family relationship. This article aims to examine the principles of interpretation, application and consistency of Saeed’s contextual interpretation in the qiwamah verse. This research is a library research with a data collection model and is presented in an analytical descriptive. The results of this study found that: First, Saeed’s contribution in contextual interpretation was a theoretical-methodological contribution by establishing nine principles in treating texts. Secondly, Saeed has applied three hermeneutical stages in interpreting verses related to male and female relationship, but it is not entirely consistent with the contextual interpretation model he initiated, especially in the third (meaning for the first recipient) and the fourth (meaning for the present). He explores the opinions of pre-modern to modern scholars more to describe the shift in context and the possibility of radically changing interpretation but he tends not to convey his personal opinion regarding the meaning of qiwamah.